Cooperation in Oiland Gas Fields between Republic of Kazakhstan and People’s Republic of China (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
“The project of a century” was called a construction in 2005 of the main pipeline of Atasu-Alashankou. The Kazakhstan-Chinese pipeline was founded by JSC KazTransOil and CNPC became the customer and the owner of the pipeline. Extent of the oil pipeline of Atasu-Alashankou made about 962,2 km. From them 960 km in the territory of the Republic of Kazakhstan and 2,2 km in the territory of the People’s Republic of China. For today, considering successful experience of construction of the oil pipeline of Atasu-Alashankou, Kazakhstan and China intend to work and realize new breakthrough projects. Demonstration of intentions of long-term cooperation ofboth countries is signing “Agreements on the basic principles of construction of the second stage of the oil pipeline Kazakhstan-China between JSC Oil Company KazMunaiGas and the Chinese National Oil Company”. This document showed sharp interest of Astana and Beijing in activization of bilateral energy cooperation.Kazakhstanparty plans construction Kenkiyak-Kumkol that becomes touch-up in connection of already existing oil pipelines of Kenkiyak-Atyrau, Kumkol-Atasu, Atasu-Alashankou, and creation of an uniform power transport corridor which will allow to transport oil from fields of the western and central Kazakhstan in the direction in the People’s Republic of China.
Keywords: Pipeline; bilateral relations; KazMunaiGas; CNPC; investments; national interests